A Mão de Deus está aqui : um estudo da Igreja Mundial do poder de Deus a partir da figura do líder Valdemiro Santiago - Leite, Maria Elizafá Sousa (2015)
This dissertation is the result of an empirical research on the World Church of God s Power and the figure of their leader Valdemiro Santiago. Founder of their church, revered for his hierarchy and the people who goes to his meetings in search of an apostle, a man with supposed powers, Valdemiro Santiago says that the hand of Good , slogan used by him, is more present in his c This institution uses a dynamic to attract a layer of society more fragile and often marginalized so them seek to provide quick solutions that are very attractive to people who are fragmented and without any without any possibility of a more critical view, regarding the alleged miracles achieved there. This analysis allowed to see the challenges that religious diversity has shown within the Pentecostal scene of our time